Australia's Seasonal Worker Program : Demand-side Constraints and Suggested Reforms - Doyle, Jesse; Howes, Stephen (World Bank Group, Washington, DC, 2015)
The Seasonal Worker Program (SWP), which was informed by the Pacific Seasonal Worker Pilot Scheme (PSWPS), represents the first effort by an Australian government to explicitly open low-skilled work opportunities to Pacific Islanders since Federation. The PSWPS was largely modelled on the success of New Zealand s equivalent RSE scheme. The PSWPS ran over a four year period in the horticulture sector (2008-2012) and had a total cap of 2,500 workers. Despite the widespread success and rapid expansion of the RSE, the PSWPS got off to a slow start and never managed to reach its full potential. This paper aims to determine whether the factors constraining demand have changed since the PSWPS and what reforms could help lift employer demand. It does so through assessing the views of a sample of employers and industry bodies across the horticulture industry. The trial sectors are not covered. The study is divided into five sections. Section two describes the origin, design and features of both the PSWPS and SWP. Section three provides a brief overview of the survey. Section four presents the key results and discusses how these compare with those collected by Hay and Howes (2012). Section five explores a possible way forward by suggesting a series of reforms based on the core set of findings.